Organization of an obstetrics unit during the COVID-19 pandemic: a short literature review - C. Zanardini; M. Papaccio; R. Castellani; R. Orabona; N. Fratelli; A. Fichera; L. Franceschetti; F. Ferrari; F. E. Odicino; E. Sartori; F. Prefiimo (Сеченовский вестник, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has posed unprecedented challenges for the delivery of high-quality obstetric services to both SARS-CoV-2 positive and negative women. The initial epidemiological pressure, especially in the most affected areas of China and Italy, led the local health services to defining care pathways based on the organizational and logistical availability of the moment. Currently, some aspects of clinical care practices and the management of women with suspected or confirmed SARS-CoV-2 virus infection are well established. The aim of this review article is to provide an outline of the suggested organization of obstetric units during the COVID-19 pandemic, and to mention the challenges we had to face at our institution.